Kecukupan Modal dan Profitabilitas Pengaruhnya Terhadap Nilai Perusahaan - Setyaningsih, Putri; Serda Rotua Silaban (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to determine how the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Assets (ROA), Operating Expenses to Operating Income (BOPO), Financing Deposits To Ratio (FDR) ) on company value with case studies of Islamic banks listed on the IDX for the 2018-2020 period. This type of research is quantitative with an explanatory research approach. The dependent variable (Y) in this study is firm value and the independent variable (X) includes Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Assets (ROA), Operating Expenses to Operating Income (BOPO), and Financing Deposit To Ratio (FDR). The type of data used in this study is secondary data derived from quarterly financial reports published by each Islamic bank listed on the IDX for the 2018-2020 period. The amount of data is 42 data obtained from 3 Islamic banks in a 3-year period. This study uses the data analysis method of multiple linear regression tests with the help of IBM Statistics SPSS 26.The research results show that the variables CAR, NPF, ROA BOPO, and FDR simultaneously have a significant effect on firm value (PBV). Partially, the CAR and FDR variables have a significant negative effect on firm value (PBV). While the NPF, ROA, and BOPO variables have no significant effect on firm value (PBV).